2021
DOI: 10.1186/s12943-021-01458-9
|View full text |Cite
|
Sign up to set email alerts
|

CircEAF2 counteracts Epstein-Barr virus-positive diffuse large B-cell lymphoma progression via miR-BART19-3p/APC/β-catenin axis

Abstract: Background Epstein-Barr virus (EBV) represents an important pathogenic factor of lymphoma and is significantly associated with poor clinical outcome of diffuse large B-cell lymphoma (DLBCL). Circular RNAs (circRNAs) play an essential role in lymphoma progression. However, the underlying mechanism of circRNA on DLBCL progression related to EBV remains largely unknown. Methods CircRNA was screened by high-throughput sequencing in tumor samples of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…However, an increasing number of studies have shown that Epstein-Barr virus infection is closely related to the occurrence of lymphoma [89]. Mechanistic analysis showed that circEAF2 specifically targets EBVencoded miR-BART19-3p, upregulates APC, suppresses downstream β-catenin expression, and counteracts EBV + DLBCL progression [90]. By regulating the nuclear translocation of β-catenin, long noncoding RNAs play a substantial role in the development of lymphoma.…”
Section: The Role Of the Wnt/β-catenin Signalling Pathway In Lymphomamentioning
confidence: 99%
“…However, an increasing number of studies have shown that Epstein-Barr virus infection is closely related to the occurrence of lymphoma [89]. Mechanistic analysis showed that circEAF2 specifically targets EBVencoded miR-BART19-3p, upregulates APC, suppresses downstream β-catenin expression, and counteracts EBV + DLBCL progression [90]. By regulating the nuclear translocation of β-catenin, long noncoding RNAs play a substantial role in the development of lymphoma.…”
Section: The Role Of the Wnt/β-catenin Signalling Pathway In Lymphomamentioning
confidence: 99%
“…Furthermore, Zhao et al. reported that CircEAF2 inhibited Epstein-Barr infection positive diffuse large B cell expansion and advanced apoptosis via the miR-BART19-3p/APC/-catenin axis ( 170 ).…”
Section: Roles Of Circrnas In Cancermentioning
confidence: 99%
“…Zhao et al. proposed that circEAF2 counteracts Epstein–Barr virus-positive diffuse large B-cell lymphoma progression via the miR-BART19-3p/APC/β-catenin axis ( 110 ). Regarding the regulated proteins, CXCR4 ( 111 113 ), APC ( 114 116 ), etc., served as important regulators in the Wnt signaling pathway.…”
Section: Roles Of Circrnas In Immune-related Diseasesmentioning
confidence: 99%